The challenge of linear time : nationhood and the politics of history in East Asia - Murthy, Viren; Schneider, Axel (Leiden series in comparative historiography ;, 2014)
The papers collected in this volume, although dealing with several different themes, congeal around a debate about the ways and extent of the dominance of linear time and progressive history and the concomitant delineation of the nation in Chinese and Japanese historiography.